2011
DOI: 10.1371/journal.pone.0023406
|View full text |Cite
|
Sign up to set email alerts
|

HSP90 Controls SIR2 Mediated Gene Silencing

Abstract: In recent years, Hsp90 is found to interact with several telomeric proteins at various phases of cell cycle. The Hsp90 chaperone system controls assembly and disassembly of telomere structures and thus maintains the dynamic state of telomere. Here, for the first time we report that the activity of another telomeric protein Sir2p is modulated by Hsp82, the ortholog of Hsp90 from budding yeast (Saccharomyces cerevisiae). In a temperature sensitive Hsp90 deficient yeast strain (iG170Dhsp82), less abundant Sir2p i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
47
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 38 publications
1
47
0
Order By: Relevance
“…Its pivotal role in telomere capping and maintenance has been established (44). Recently, work on Sir2 protein dynamics as a function of Hsp82 activity has recognized a link between Hsp82 and telomere silencing (38). Two recent studies on Sba1 and Aha1, two important cochaperones of Hsp82, have unraveled an interesting connection with DNA repair proteins.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Its pivotal role in telomere capping and maintenance has been established (44). Recently, work on Sir2 protein dynamics as a function of Hsp82 activity has recognized a link between Hsp82 and telomere silencing (38). Two recent studies on Sba1 and Aha1, two important cochaperones of Hsp82, have unraveled an interesting connection with DNA repair proteins.…”
Section: Discussionmentioning
confidence: 99%
“…For the temperature-sensitive strains, the cells were divided into two groups; one part was incubated at 25°C for 4 h, and another part was incubated at 37°C overnight. After that, equal numbers of cells were taken and precipitated, and protein was isolated from them by the trichloroacetic acid (TCA) method, followed by Western blotting (38). A rabbit anti-Rad51 antibody (Promega), a mouse anti-Hsp82 antibody (Calbiochem), and a mouse anti-Act1 antibody (Abcam) were used at a 1:5,000 dilution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Hsp82 null condition not only leads to the reduced abundance of Sir2 but also results in the inactivation of Sir2 proteins. On the other hand, Hsp82 overexpression leads to the reduction of the steady-state level of Sir2 protein, though it does not affect the mating type silencing activity of Sir2 (5). In this report, we provide mechanistic insights into Hsp82 overexpression phenotype which occurs while cells are exposed to heat shock.…”
mentioning
confidence: 79%
“…Sir2 deacetylates histone H3 (at K9, K14, and K56) and H4 (particularly K16) to regulate telomeric heterochromatin structure in yeast (3,4). Our previous studies have demonstrated that heat stress and concomitant overexpression of Hsp90 result in euchromatinization of silent subtelomeric chromatin by reducing the steady-state level of Sir2 (5).…”
mentioning
confidence: 99%